PENINGKATAN HASIL BELAJAR SISWA PADAPEMBELAJARAN IPA MELALAUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Fatrina, Wengsi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research was classroom action research using quantitative and qualitative approaches. The results of the planning cycle average of 79.1%, while in the second stage of the planning cycle increased 93%. Aspects of the implementation phase of the first cycle teachers with an average of 73.7%, while in the second stage of the implementation cycle aspects of teachers increased to 95%. In terms of the first cycle of students gained an average of 72.5%, while in the second cycle increased to 95%. Cognitive assessment in the first cycle an average of 64.6 61.4 affective test results.Whereas 62.4 psychomotor tests of cognitive assessment in the second cycle increased to an average of 83.7 82.6 affective test results. 83.7 psychomotor tests. Kata  Kunci: hasil belajar, IPA, model kooperatif tipe jigsaw